(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Notion Of S- Valued Graphs Developed In The Year 2015. Later We Study The Different Products In S-Valued Graphs. In Particular, We Studied The Concept Of S-Valued Graphs By Means Of Cartesian Product. In This Paper, We Precede The Idea Of S• Valued Graphs And Their Cartesian Product Along With Some Regularity Conditions.